Reflections on Environmental Bioethics - Ferreira Carvalho, Fernanda Maria; Pessini, Léo; Campos Junior, Oswaldo (O Mundo da Saúde, 2006)
The magnitude Bioethics has now reached is being disclosed by its diversity of topics. It blossoms and evolves in a accelerated and continuous way in the events and specific debates that happen in the world as a whole, disclosing the plethora of complex moral concerns in the fields of medicine, of human health and the environment. This communication aims to awake, to extend and to concentrate for a reflection on the importance of the subjects linked to the intersection between Bioethics and the Environmental Sciences.